De chaque côté de la surface - Johnny Samuele Baldi (Temporalités)
This paper focuses on some considerations about the temporal, stratigraphic and epistemological relationships between the archaeological surface (and the ceramics materials collected during the preliminary prospection) and underground levels (and their information). Therefore, this paper is not a specific study, nor a detailed discussion of a methodological problem. It is rather a series of reflections on contradictions implicit to some archaeological approaches : linear reading of time, linear evolutions, application of typical (even if useful) Western epistemological tools and ideas to a non-Western context, absence of archaeological interest for the current materiality (on the surface). The traditional linear temporality (based on the notion of a Great Divide between past and present, antiquity and “modernity”), is strictly linked to the assumptions of an old colonial linear evolutionism and it creates some archaeological aporias that can be overcome by the adoption of a non-linear and “flattened” temporality. Some archaeological evidence are briefly presented to show that technological and cultural changes are often non-linear, as well as that current material-cultural conditions can be explored with an archaeological approach.